Clinical study of hydatid disease - Pothare, Amit N.; Deshpande, Amol V.; Nandu, Vipul V. (International Surgery Journal, 2016)
Background:Hydatid cyst is zoonosis caused due to Echinococcus species Echinococcus granulosus. In developing countries like India, Iran, China and Mediterranean countries it is still remains a major problem. It can involve any organ and can mimic almost any pathological condition. Complication associated rather than disease itself, are difficult to treat. Aims was to study about; (1) The major organs involved by hydatid disease. (2) The best treatment modality depending upon the site, size and organ involving the cyst. (3) The preoperative and postoperative complications of hydatid disease. Methods: Prospective clinical study was conducted on 58 patients. All patients diagnosed as hydatid disease mainly by ultrasound or CT scan and then treated either operatively or non-operatively were included in this study. The choice of surgical procedure was guided by site, size, organ involving the cyst and associated complications. The patients were followed up for a period of 6 months. Results:The highest incidence was found in 3rd decade (27.59%). It is more common in females (70.69%). Liver is most common organ involved (86.2%). Ultrasonography was the imaging modality of choice for diagnosis. Partial cystectomy with omentoplasty with external drainage was most commonly performed surgery after through irrigation with scolicidal solution. Presence of cystobiliary communications was most common intra-operative complication (22%). The mean duration of stay after surgery was about 9.34 days. Conclusions:Hydatid disease is still a major problem in rural agricultural population. Surgery is most widely acclaimed procedure for treatment of hydatid.